Causal Effects of Education on Marriage - Kunwon Ahn; John V. Winters (Institute of Labor Economics (IZA), 2025)
Many nations have experienced both rising education levels and declining marriage rates. However, cross-sectional comparisons within countries often indicate that more highly educated individuals are more likely to be married. Economic theory suggests ambiguous causal effects of education on marriage. This study uses a novel instrumental variable approach and finds that education decreases the probability of being married for younger persons but not for older persons. However, education increases the probability of never marrying even by ages 45-54. Education also reduces the likelihood of being divorced or separated, which partially offsets effects on being never married in overall marriage rates.
Keywords: I20; J12; J24; 330; marriage; education; human capital; instrumental variables